Study the characteristic of antenna by different material on simple ADS-B receiver / Nurulain Mohd Yunus. - Mohd Yunus, Nurulain (2013)
This thesis presents, study the characteristic of antenna by using different material on simple ADS-B receiver. In the recent years, the era of aviation technologies is come into a new technology to provide specialized Air Traffic Management (ATM) system. Nowadays, the air traffic is expected to increase that may be a higher in certain area of the country. As to fulfilled requirement of ADS-B system, the antenna configuration is needed to be determined in terms of elements in array. In this paper presents, study the characteristic of antenna by using different material on simple ADS-B receiver for implementing these systems and the benefits that were achieved. By doing this project, aluminum and copper antenna is needed to identify the effect on simple ADS-B receiver. Different antenna material will produce different result on the sbsplotter.